Detection of the SARS‐CoV‐2 D614G mutation using engineered Cas12a guide RNA. Issue 6 (9th March 2021) - Meng, Qingzhou; Wang, Xinjie; Wang, Yanqun; Dang, Lu; Liu, Xinyi; Ma, Xiaodong; Chi, Tian; Wang, Xian; Zhao, Qin; Yang, Guang; Liu, Ming; Huang, Xingxu; et al.
Abstract: Detection of pathogens with single‐nucleotide variations is indispensable for the disease tracing, but remains technically challenging. The D614G mutation in the SARS‐CoV‐2 spike protein is known to markedly enhance viral infectivity but is difficult to detect. Here, we report an effective approach called "synthetic mismatch integrated crRNA guided Cas12a detection" (symRNA‐Cas12a) to detect the D614 and G614 variants effectively. Using this method, we systemically screened a pool of crRNAs that contain all the possible nucleotide substitutions covering the ‐2 to +2 positions around the mutation and identify one crRNA that can efficiently increase the detection specificity by 13‐fold over the ancestral crRNA. With this selected crRNA, the symRNA‐Cas12a assay can detect as low as 10 copies of synthetic mutant RNA and the results are confirmed to be accurate by Sanger sequencing. Overall, we have developed the symRNA‐Cas12a method to specifically, sensitively and rapidly detect the SARS‐CoV‐2 D614G mutation. Abstract : Detection of pathogens with single‐nucleotide polymorphisms (SNP) is indispensable for the disease tracing, but remains technically challenging. In this study, the authors report an effective approach called "synthetic mismatch integrated crRNA guided Cas12a detection" (symRNA‐Cas12a) to detect the D614 and G614 variants of SARS‐CoV‐2 effectively. The use of this optimizing strategy enables the symRNA‐Cas12a to become a powerful assay for monitoring the SNP.